Review of diagnostic uses of shunt fraction quantification with technetium-99m macroaggregated albumin perfusion scan as illustrated by a case of Osler–Weber–Rendu syndrome - Chokkappan, Kabilan (Ann Thorac Med, 2016)
Bilateral pulmonary arteriovenous malformations (AVMs) are rare and are often associated with the hereditary hemorrhagic telangiectasia (HHT/Osler–Weber–Rendu) syndrome. We present a woman who presented with neurological symptoms due to a cerebral abscess. On further evaluation, bilateral pulmonary AVMs were identified. The patient was diagnosed with HHT, based on positive family history and multiple cerebral AVMs recognized on subsequent catheter angiogram, in addition to the presence of bilateral pulmonary AVMs. Craniotomy with drainage of the brain abscess and endovascular embolization of the pulmonary AVMs was offered to the patient. As a preembolization work-up, the patient underwent nuclear lung perfusion scan with technetium-99m macroaggregated albumin (Tc-99m MAA) to assess the right-to-left shunt secondary to the pulmonary AVMs. Postembolization follow-up perfusion scan was also obtained to estimate the hemodynamic response. The case is presented to describe the role of Tc-99m MAA perfusion lung scan in preoperatively evaluating patients with pulmonary AVMs and to emphasize on the scan's utility in posttreatment follow-up. Various present day usages of the Tc-99m MAA lung perfusion scan, other than diagnosing pulmonary thromboembolism, are discussed. Providing background knowledge on the physiological and hemodynamic aspects of the Tc-99m MAA lung perfusion scan is also attempted. Various imaging pitfalls and necessary precautions while performing Tc-99m MAA lung perfusion scan are highlighted.